Unity for absolute beginners - Blackman, Sue (Apress, 2014)
Unity for Absolute Beginners walks you through the fundamentals of creating a small third-person shooter game with Unity. Using the free version of Unity to begin your game development career, you'll learn how to import, evaluate and manage your game resources to create awesome third-person shooters. This book assumes that you have little or no experience with game development, scripting, or 3D assets, and that you're eager to start creating games as quickly as possible, while learning Unity in a fun and interactive environment. With Unity for Absolute Beginners you'll become familiar with the Unity editor, key concepts and functionality. You'll learn how to import, evaluate and manage resources. You'll explore C# scripting in Unity, and learn how to use the Unity API. Using the provided art assets, you will learn the fundamentals of good game design and iterative refinement as you take your game from a simple prototype to a quirky, but challenging variation of the ever-popular first-person shooter. As can be expected, there will be plenty of destruction, special effects and mayhem along the way. Unity for Absolute Beginners assumes that you have little or no experience with game development, scripting, or 3D assets, but are eager to get up-to-speed as quickly as possible while learning Unity in a fun and interactive environment.